Subdirectly irreducible double Km,n-algebras - Mendes, C. (2016)
In this paper we study subdirectly irreducible double Km,n-algebras. In particular, we prove that every finitely subdirectly irreducible double Km,n-algebra is subdirectly irreducible and we characterize subdirectly irreducible double Km,n-algebras by determining their lattice of congruences.